Age and fasting blood sugar levels are associated factors for mindful eating among Type 2 diabetes mellitus patients during COVID-19 pandemic confinement. - Nurul Hayati Chamhuri; Noorlaili Mohd Tohit; Amirah Azzeri; Norshamliza Chamhuri; Siti Rohani M Alias (PLoS ONE, 2022)
The COVID-19 pandemic has impacted the eating behaviours of many people, especially Type 2 Diabetes Mellitus (T2DM) patients. This study aimed to determine the level of mindful eating and its associated factors among T2DM patients at a primary care clinic near Kuala Lumpur. A cross-sectional study was conducted from 18th December 2020 to 5th March 2021 during the movement control order in Malaysia. Respondents were recruited using systematic random sampling via an electronic appointment system. They completed a questionnaire consisting of sociodemographic, clinical profiles, and a Malay-translated Mindful Eating Questionnaire (MEQ-M). Their blood pressure and body mass index were taken during the appointment day while the remaining clinical profiles such as fasting blood sugar (FBS) were obtained from the medical record. Two hundred respondents were recruited with a mean (SD) age of 57.0 (10.90) years. More than half of them were female (54%). Two-thirds of them had uncontrolled diabetes based on elevated FBS of >7 mmol/L (61.5%) and glycated haemoglobin (HbA1c) of >7% (67%), respectively. The mean (SD) score for mindful eating was 2.9 (0.25). Multiple logistic regression revealed that older respondents had a higher level of mindful eating [(AOR = 1.05, p-value 0.01, 95% CI = 1.01-1.09)]. In addition, elevated FBS level was also associated with a greater level of mindful eating [(AOR = 2.55, p-value 0.01, 95% CI = 1.28-5.07)]. Therefore, healthcare providers should promote mindful eating during the consultation, especially among younger patients. Blood glucose monitoring is also recommended to instil awareness of the importance of healthy eating habits.